Student Life Skills Development Through Scouting Extracurricular Activities (Case Study at Vocational High School SMK Teknologi Industri Pembangunan Cimahi) - Tresi Tiara Intania Fatimah (Empowerment : Jurnal Ilmiah Program Studi Pendidikan Luar Sekolah, 2020)
The purpose of this research is to know the development of students' life skills through extracurricular scout activities in preparation for interacting in the community, in addition to having  skills in academic field  students must also be equipped with various life skills. The Scout Movement is one form of non-formal education that aims to help students as part of the community in order to understand the values, attitudes, knowledge and functional skills necessary to build a nation's life and state. The method of research used is qualitative research through case studies conducted by conducting research in the field directly, interviews and documentation studies on the implementation of education of life skills through an extracurricular scout activities at Vocasional High School SMK Teknologi Industri Pembangunan Cimahi.